The role of social media as information infrastructure for the integration and information practices of migrant communities - Khai, Romuana; Lalhruaitluanga, H.; Vanamamalai, Ratnamala (Faculty of Communication, Padjadjaran University, 2026)
Background: Chin migration from Myanmar to Mizoram has intensified due to political instability. Understanding how displaced populations develop information practices and navigate information barriers through digital platforms addresses critical gaps in Library and Information Science (LIS) research within migration contexts.Purpose: This study investigates information practices of Chin migrants in Aizawl, examining how social media platforms function as alternative information infrastructure supporting everyday life information seeking (ELIS), information literacy development, and participation in transnational information communities.Methods: Convergent mixed-methods research employed questionnaire surveys of 256 Chin migrants (206 adolescents aged 13–18; 50 adults aged 19+) selected via purposive and snowball sampling across four Aizawl localities, supplemented by five semi-structured key informant interviews. Quantitative data were analyzed using SPSS; qualitative data underwent thematic analysis following Braun and Clarke's framework.Results: YouTube (100%), WhatsApp (93%), and Instagram (88.8%) emerged as primary information sources among adolescents, functioning as hybrid information ecosystems. Social media facilitated information-mediated integration: 68.4% reported digital platforms enabled access to local cultural information, while 71% acquired Mizo cultural knowledge through informal digital channels. However, significant barriers persist, including limited information literacy competencies, constrained device access, misinformation exposure, and language-based exclusion.Conclusions: Social media operates as alternative information infrastructure where migrants develop sophisticated information practices to navigate complex information landscapes under displacement conditions. Findings demonstrate how marginalized populations construct information resilience when formal institutions remain inaccessible. Effective information services for displaced populations require: recognition of social media as legitimate infrastructure; mobile-optimized multilingual resources; community-based information literacy instruction; and library-NGO-community partnerships addressing systemic access barriers.